Two-phase Solvothermal Synthesis of MoO2/RGO Nanocomposites for Lithium-Ion Battery Anodes. Issue 1 (March 2021) - Geng, Qin; Su, Xintai; Dong, Fan; Wang, Zhiming
Abstract: Nowadays, it is necessary to develop the lithium-ion battery with higher capacity, lighter weight and thinner volume. Transition metal oxide, as a promising anode materials, has drawn much attention, as a result of its large capacity and high economic value. However, poor cycle stability greatly limits its practical applications. In this paper, MoO2 /RGO nanocomposites were synthesized by a two-phase solvothermal method by adjusting the pH value to 2.0. Affected by the size of nanoparticles, the nanocomposites with MoO2 nanoparticles (100 nm) uniformly anchored on the RGO nanosheets exhibit a more superior electrochemical performance with a high capacity of 765.1 mAh g −1 after 50 cycles, which is expected to be a promising anode material for lithium-ion batteries.